2019
DOI: 10.1177/0160017619863476
|View full text |Cite
|
Sign up to set email alerts
|

Toward Job or Amenity?: Evaluating the Locational Choice of Internal Migrants in China

Abstract: This study provides new evidence on the debate of job opportunities versus urban amenities in determining the locational choice of migrants. We employ a conditional logit model to generate credible estimates, using two large representative data sets on China’s internal migrants. Our findings confirm that both job opportunities and amenities play consistent and salient roles in the geographical choice of internal migrants, while highly skilled migrants tend to attach more importance to urban amenities. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…on migration have been well documented [25][26][27]. More recent research has shown that factors such as climate, temperature, and ambient air quality can also significantly affect migrants' decisions [28][29][30].…”
Section: Literaturementioning
confidence: 99%
“…on migration have been well documented [25][26][27]. More recent research has shown that factors such as climate, temperature, and ambient air quality can also significantly affect migrants' decisions [28][29][30].…”
Section: Literaturementioning
confidence: 99%
“…A few studies have focused on the role of city amenities in determining the migration behavior and intentions. In particular, on the debate of job opportunities versus urban amenities in determining the locational choice, Su et al (2019) employed a conditional logit model on China's internal migrants and found out urban amenities are more crucial [29]. Shao and Chen (2014) found that a good health care environment in the region is conducive to ensure and improve the labor output [30], which is an important guarantee variable for overseas high-level young returned talents to fulfill their life demands.…”
Section: Urban Amenity and Location Choicementioning
confidence: 99%
“…As big cities are often accompanied by higher living costs and inevitable “urban disease”, some second-tier cities might tend to be more attractive for young populations. Hence, attractiveness of current cities is not driven by jobs or economics only, factors concerning the direction of population movement are playing increasingly important roles in defining the attractiveness of a city [ 19 21 ].…”
Section: Related Workmentioning
confidence: 99%